2014
DOI: 10.5812/ircmj.18346
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Prevention Regarding Sexually Transmitted Infections and its Predictors in Women

Abstract: Background:Sexually transmitted infections (STIs) have a major negative impact on sexual and reproductive health globally. The most effective way to avoid STIs is to abstain from sexual contact or having sex only in a long-term, mutually monogamous relationship with an uninfected partner.Objectives:This study aimed to determine behavioral prevention regarding STIs.Patients and Methods:This analytic cross-sectional study was performed on 584 women aged 15-49 referring to health care centers of Tabriz-Iran in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…There were 24 items about awareness of GWs. The reliability of this part of the questionnaire was tested by Farshbaf et al among women in Tabriz City and was found to be 82% [ 32 ]. Items enquiring about the awareness of GWs were rated on a three-point Likert type (True, False, Don’t Know).…”
Section: Methodsmentioning
confidence: 99%
“…There were 24 items about awareness of GWs. The reliability of this part of the questionnaire was tested by Farshbaf et al among women in Tabriz City and was found to be 82% [ 32 ]. Items enquiring about the awareness of GWs were rated on a three-point Likert type (True, False, Don’t Know).…”
Section: Methodsmentioning
confidence: 99%
“…In recent study, factors associated with practice, based on multiple linear regression, included father's education and employee occupation, families' income, history of sexual abuse in childhood, husband's education, places of supplying condoms, condoms use, duration of staying at this job, accessing ways of client and the usual working times. The study of Farshbaf et al on women referring to Tabriz-Iran health centers showed that the scores of preventive behavior were increased with the increased level of education and income [22]. The study of Ghezelsaflou et al in Eslamshahr showed that adolescents with a childhood history of sexual abuse develop more high-risk behaviors [35].…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire of practice was a researcherdesigned instrument developed based on a review of the related literature [21][22][23][24]. This questionnaire examined the practice regarding STIs of sex workers including 13 four-choice items including never (score=1), sometimes (score=2), almost (score=3) and always (score=4).…”
Section: Data Collectionmentioning
confidence: 99%
“…The sample size for BP predictors, using G-power and considering α = 0.05, β = 0.05, effect size = 0.097, and two-tailed hypothesis, was estimated as 111. [ 21 ]…”
Section: Methodsmentioning
confidence: 99%